Identification of Potentially Inappropriate Medications in Frail Older Adults Residing in Long-Term Care: A Retrospective Chart Review Study - Clara H. Heinrich; Suzanne McCarthy; Sheena McHugh; Maria D. Donovan (Adis, Springer Healthcare, 2022)
Abstract Introduction Deprescribing is associated with positive health outcomes for older adults in long-term care (LTC), however deprescribing is not universally implemented. Objective The primary aim of this study was to estimate the prevalence of potentially inappropriate medications (PIMs) prescribed to frail older adults in Irish long-term care facilities (LTCFs), as identified by the Screening Tool of Older Persons Prescriptions in Frail adults with limited life expectancy, version 2 (STOPPFrail v2). Methods A retrospective chart review was conducted in two publicly funded LTCFs in Ireland. Eligible participants were those (1) ≥ 65 years of age; (2) resident in a LTCF; (3) eligible as per the STOPPFrail v2 criteria by the site's Medical Officer; and (4) receiving regular medication. Data collected included age, sex, drug, dose, frequency, regular/pro re nata prescribing and indication/relevant diagnoses. Rates of polypharmacy (taking five or more medications) and excessive polypharmacy (taking 10 or more medications) were calculated. STOPPFrail v2 was used to identify PIMs; however, clinical measurements were not taken. Descriptive and association statistics were calculated. Results Of the 103 residents, 89 were ≥ 65 years of age and categorised as frail and were therefore eligible for inclusion in the study. Of those eligible, 85 (95.5%) had polypharmacy and 57 (64%) experienced excessive polypharmacy. The mean number of regular medications was 10.8 (± 3.8), total medications 17.7 (± 5) and diagnoses 5.5 (± 2.5). The mean number of PIMs per resident was 4.8 (± 2.6). Of the eligible participants, 59.6% had at least one medicine without a documented indication, while 61.8%, 42.7% and 30.3% had at least one PIM from the vitamin D, antihypertensives and proton pump inhibitors drug classes, respectively. Conclusion Medication and PIM use was high among LTC residents, with inappropriate polypharmacy of concern. Lack of clear indication for prescribing medications appears to be an issue in LTC, potentially affecting healthcare professionals' engagement with deprescribing. The prevalence of PIMs may be overestimated in the antihypertensives/antidiabetic classes due to the lack of clinical measurements.